(untitled) (Bangladesh Journal of Otorhinolaryngology, 2010)
This study was carried out to assess the graft take rate as well as hearing improvement after myringoplasty with temporal fascia graft by underlay technique. Study was done in department of ENT and Head-Neck Surgery of BSMMU, Dhaka Medical College Hospital and BIRDEM from July 2006 to June 2007. Sixty (60) patients were included prospectively for this work. In this study graft take rate was 85% (51 out of 60) and graft failure was 15% (9 out of 60). The age range of the patients was 10 to 50 years. Highest number of patients was in the age group of 21 to 30 years and graft take was also maximum in this age group. Graft take rate of small size perforation (100%) and medium size perforation (93.23%) had more than subtotal perforation (77.77%). Success rate of posterior perforation was maximum (93.75%) followed by anterior perforation (88.23%). In case of approach of operation postaural approach had maximum success rate (88.09%) followed by endaural (75%) and transcanal approach (80%). In this study the mean pre and postoperative air conduction threshold in the successful cases were 34 dB and 24 dB respectively, with a mean audiological improvement of 10 dB. Improvement of mean air bone gap was 11 dB. Of the successful cases hearing was improved in 31 patients (60.78%) and 20 patients (39.21%) showed no significant hearing improvement. From this study it can be concluded that myringoplasty is a valid treatment modality for tympanic membrane perforation. Keywords: Myringoplasty; Graft take rate; Hearing improvement DOI: 10.3329/bjo.v16i1.5777 Bangladesh J Otorhinolaryngol 2010; 16(1): 23-28